Effect of rice types on various properties of germinated rice ice cream - Boonterm,A. (Chiang Mai University, 2015)
Three different types of germinated rice, including brown rice, red rice and purple rice, were utilized in this research to make ice creams. The ice cream making was started by soaking the rice grains for 5 h at room temperature, blending the grains with the soaking water and filtering it to produce rice milk. The rice milk was then heated, added with other ice cream ingredients (sugar, a stabilizer and coconut milk) and held at 70oC for 2 min. The cooled ice cream mixture was blended in a blender for 3 min before processing the mixture in an ice cream machine. The final ice cream product was stored at -18°C for different analyses. Using germinated brown rice, the final ice cream product significantly had the highest overrun and pH values with the lowest b* and moisture content values compared to the other two ice creams. Different types of germinated rice did not significantly affect the melting rate, hardness, total soluble solid, protein and microbial contents of the final ice creams. When a sensory panel evaluated the three types of ice cream, the panelist team could significantly differentiate the color and smoothness of the ice cream samples. A supplementation of 5% (w/w) cooked rice particles in the germinated brown rice ice cream significantly increased the ice cream hardness with a significant reduction in the melting rate, pH, total soluble solid and moisture content values compared to the corresponded ice cream without rice particles.